2015
DOI: 10.3390/ma8095319
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Studies of Palm Oil Mill Waste Aggregates for the Construction Industry

Abstract: The agricultural industry in Malaysia has grown rapidly over the years. Palm oil clinker (POC) is a byproduct obtained from the palm oil industry. Its lightweight properties allows for its utilization as an aggregate, while in powder form as a filler material in concrete. POC specimens obtained throughout each state in Malaysia were investigated to evaluate the physical, chemical, and microstructure characteristics. Variations between each state were determined and their possible contributory factors were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…It was obtained in form of large chunks with rough and porous surfaces. In general, POC was disposed in the landfills or used as road covers near the palm plantation due to the fact that POC has little commercial value [21], [22]. Unlike BA, the amount of POC produced is yet to trigger alarming concerns.…”
Section: Fig 1 Plumes Of Dms That Have Caused Turbiditymentioning
confidence: 99%
“…It was obtained in form of large chunks with rough and porous surfaces. In general, POC was disposed in the landfills or used as road covers near the palm plantation due to the fact that POC has little commercial value [21], [22]. Unlike BA, the amount of POC produced is yet to trigger alarming concerns.…”
Section: Fig 1 Plumes Of Dms That Have Caused Turbiditymentioning
confidence: 99%
“…The self-compacting mortar mixture (SCM) can provide many advantages. Self-compacting mortar, as the name indicates is a highly flowable mortar which can be placed without any external consolidation [5]. Nowadays, the self-compacting mortar is specially designed for repair applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…POC, when crushed, represents a lightweight aggregate that can be potentially used in concrete production [8]. [9] reported that the similarity of the particle size distribution and the grading features of sand and POC fine aggregate indicate the suitability of POC fine as a suitable substitution for sand in concrete production. Abdullahi et al (2008) [10] prepared trial mix proportions for POC, and showed that it is possible to use POC as an aggregate in the mix design of concrete without adding admixture.…”
Section: Pam Oil Clinker (Poc)mentioning
confidence: 99%